Implementation of Public Services: Terapeutic Communication of Health Professional to Patients in Serang Regency - Ditha Prasanti; Ikhsan Fuady (Jurnal Pekommas, 2019)
Health service is the main factor that supports the success of development of a region. Various health promotion programs have been carried out in order to succeed in optimizing public services. The purpose of this research is to reveal the implementation of public service held by the health professionals to the patients at Tunjung Teja Puskesmas, Serang District. The research is a case study with a qualitative approach. The study results that there was implementation of public services in therapeutic communications held by the health professionals to the patients in the Tunjung Teja Public Health Center, Serang District, such as the infrastructure services, therapeutic communication services, and information services.